The effects and mechanism of environmental enrichment on MK-801 induced cognitive impairment in rodents with schizophrenia - Xu, Jinwei; Li, Yaohao; Tian, Biqing; Liu, Haiying; Wu, Shengxi; Wang, Wenting (Frontiers in Cellular Neuroscience, 2022)
Schizophrenia is a severe mental disorder characterized by positive, negative, and cognitive symptoms. Cognitive symptoms are a kind of symptoms with high incidence and great impact on patients. There is no effective treatment in clinical practice. N-methyl-d-aspartic acid (NMDA) receptor hypofunction may be an important cause of cognitive symptoms. MK-801 (also named Dizocilpine), a noncompetitive antagonist of NMDA receptor, is often used to construct a model of NMDA receptor dysfunction. In terms of treatment, environmental enrichment (EE) as an environmental intervention can effectively improve the symptoms of cognitive impairment in rodents. In this paper, we first briefly introduce the background of cognitive symptoms and EE in schizophrenia, and then investigate the manifestations of MK-801 induced cognitive impairment, the improvement of EE on these cognitive impairments based on the MK-801 induced schizophrenia rodent models, and the possible mechanism of EE in improving cognitive symptoms. This article reviews the literature in recent years, which provides an important reference for MK-801 to construct a cognitive symptom model of schizophrenia and the mechanism of EE in improving cognitive symptoms of schizophrenia.